Figures of pathos Festschrift in honor of Elisabeth Bronfen - Berndt, Frauke 1964-; Karremann, Isabel; Müller-Wille, Klaus 1966- (Königshausen & Neumann, 2023)
"As a Festschrift for Elisabeth Bronfen’s sixty-fifth birthday, this volume gathers a series of essays by her friends and colleagues on forms and functions of pathos, which play a central role in the scholarly and artistic work of the honoree. πάθος [Pathos] is the way in which words and images have the power to move us, and through which aesthetic representation becomes an affective experience. The essays explore the potential of this concept from antiquity to the present and the power of pathos in different media." (Buchrückseite)